Residual mining waters in the safety of the orange cultivated to surroundings of the yellow river - Cuenca Mendoza, Mary (2019)
This is an original article that manifests as the vegetation cultivated near the Amarillo river, absorbs the reagents used in flocculation in mining activity that are: Cyanide (CN) and Mercury (Hg); these means are by infiltration, irrigation, and by winter time when the flow is greater and increases, reaching the crops that are on its banks. Reference samples of the orange (citrus sinensis) were collected, and through these results the high concentration of these reagents was evidenced exceeding the maximum levels for heavy metals proposed by FAO and WHO. The assimilation occurs gradually in the process of absorption of nutrients from the plant and is evaded by it to a certain concentration, however, when exceeding it produces an overload to the stem, leaves, flowers, reaching the fruit and causing an alteration in the Photosynthesis, growth and uptake of Potassium (K), which are consumed and marketed by the local community producing a biomagnification of heavy metals in their organisms causing serious damage to their health that are not yet visible.